Konsep Pendidikan Anak Dalam Islam (Perspektif Syaikh Musthafa Al-Adhawi Dalam Kitab Fiqhu Tarbiyyat Al-Abna’) - Nur Wakhidah; Muhammad Arfan Muammar; Zainal Arifin (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
: A child is a gift from Allah swt that is dreamed of in a home. A healthy and happy child is every man's dream. The problem that occurs a lot at this time is that very modern life opens a wide perspective for the younger generation. With the ease of access to get a variety of information, of course, there are positive impacts and also negative impacts. One of the negative impacts when the younger generation can not filter what they should adopt from the internet. Here the role of parents in educating is needed. Therefore, it is important to study more in the literature, especially those that are widely sourced from Islam, both books and muslim intellectuals about child education to broaden the scientific horizons of teachers in their role in child education in Islam. The purpose of the author in this article is to help parents and teachers in providing Islamic education. Khsusunya about the concept of child education in islam perspective Shaykh Musthafa al-Adhawi in the book of fiqhu tarbiyyat al-abna and its relevance in the contemporary era. In this study the authors used quantitative methods with a descriptive approach. With the object of research is the book of fiqh tarbiyyat al-abna. The results showed that the concept of Islamic education in the book of fiqhu tarbiyyat al-abna is still relevant in the contemporary era.